INDUSTRIAL POLICY AND INTERNATIONAL BUSINESS DYNAMICS: A COMPARATIVE ANALYSIS OF INDIA’S PRE- AND POST-NATIONAL MANUFACTURING POLICY 2011 - Gupta, Amitabh; Shakya, Anurag (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper investigates the impact of India's National Manufacturing Policy (NMP) 2011 on international business dynamics, comparing trends in trade, foreign direct investment (FDI), and global partnerships before and after the policy's implementation. “The NMP was introduced to transform India into a global manufacturing hub by fostering growth in the sector through improved infrastructure, policy incentives, and a streamlined regulatory framework. This study examines whether these provisions led to significant changes in India’s international trade patterns and investment inflows. A comparative analysis reveals mixed results, showing modest increases in FDI and partnerships in certain sectors but limited effects on import dynamics, contradicting expectations. While the NMP aimed to attract global businesses and reduce import dependency, data suggests that domestic structural challenges, including inadequate infrastructure and inconsistent policy implementation, hindered these outcomes. The findings indicate that, while the NMP contributed to incremental growth in specific areas, it fell short of substantially reshaping India’s position in the global market or significantly impacting import volumes. This analysis offers critical insights into the practical challenges of industrial policy execution in emerging economies, highlighting the gap between policy intent and economic impact. Additionally, it underscores the need for comprehensive policy frameworks that address underlying structural issues to achieve substantial trade and investment transformations. This study concludes by suggesting that India’s future industrial policies could benefit from a more integrated approach, incorporating targeted infrastructure development, streamlined regulatory processes, and robust implementation mechanisms to achieve sustainable industrial growth and enhance global competitiveness.